Innovative Context-Based Sociology Learning Media Assisted by Smart Apps Creator for High School Students - Erna Retna Safitri; Ridhah Taqwa; Yulasteriyani (Attractive : Innovative Education Journal, 2026)
Difficulty in understanding the meaning and benefits of the material studied in sociology concepts underlies the need for innovative learning models, especially by integrating technology. This study aims to develop Context-Based Learning Media Assisted by Digital Applications SAC (Smart Apps Creator) for high school students through a thorough needs analysis process. The research was conducted using a research and development approach. The development model used is the ADDIE model. Data collection techniques were carried out through observation, interviews, and questionnaires using observation sheets, interview guides, and questionnaires as instruments. Respondents involved in this study included principals, teachers, and students from 2 high schools in 2 regencies, namely Ogan Ilir Regency and North Ogan Komering Regency, with a total of 82 respondents. Data analysis was conducted using qualitative and quantitative analysis. The results of the needs analysis indicate that the development of interactive, context-based learning media is necessary to support more contextual and meaningful Sociology learning. The validation results on the aspects of media, content, and language show that the developed media has high validity in all three aspects with an average score of 4.6. The study also shows that the developed media is effective in improving students' learning outcomes, with an N-gain of 0.67, which is categorized as moderate. These results can serve as a reference for ideas in analyzing the practicality and effectiveness of using learning media as one of the development products in educational technology.